Analysis of the Potential and Problems of the Mandangin Islands As a Tourism Village in Support of the Dewi Cemara Program - Faraby, Muhammad Ersya; Karim, Moh. (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze the potential and problems of the Mandangin Islands as a Tourism Village in Supporting the Dewi Cemara Program (Tourism Village whose Communities are Intelligent, Independent and Prosperous). The purpose of this program is to encourage rural-based economic growth centers, where activities are supported by the motivation and enthusiasm of the community and various facilities, the existence of objects and attractions, having physical access and market access, having the potential for partnerships, and the availability of public facilities. Researchers will conduct a research as a step to find out the potential and problems on Mandangin Island in supporting the Dewi Cemara Program, by determining Mandangin Village as the object of research. The approach used in this study uses a descriptive qualitative approach with a case study method, additional data collection is carried out by studying literature from various sources, both printed and statistical databases, with data collection methods in the form of interviews, observation, and documentation. The theory of identification of potentials and problems to dissect the supporting instruments of the Dewi Cemara Program on Mandangin Island. Technically, the researcher will mapping the informants consist of Head of DISPORABUDPAR Sampang, Head of POKDARWIS Sampang, Head of Mandangin Village, Tourists and the local community at Mandangin. In this case the researcher wants to absorb their aspirations. The mandatory achievement target in this research is one article published in a national scientific journal accredited at least SINTA 4.